Salinity impacts on experimental fodder sorghum production (SAARC Journal of Agriculture, 2018)
Field experiment was conducted at research station of Soil, Water & Environment Discipline, Khulna University, during the dry season to see the growth performance of sorghum (Sorghum bicolor L. cv. Morokoshi) irrigating with saline water. For irrigation, river water (RW) containing EC value of 14.04 dS m-1 was collected from the Rupsha river, Khulna and mixed with tap water [TW] containing EC value of 0.78 dS m-1at three different ratios (3:1, 1:1 and 1:3 v/v). After mixing, water containing five different EC values (0.78, 4.19, 7.18, 10.79 and 14.04 dS m-1) were obtained and considered as salinity treatment. Harvesting and sampling was done 83 days after transplanting (DAT) by cutting four sorghum plants randomly selected from each plot. Different morphological parameters such as plant height, leaf number, leaf length, leaf width, stem diameter and plant biomass were measured and recorded. Soil samples were also collected from each plot. Under water salinity stress, all the agronomic attributes and plant biomass showed a decreasing tendency with increasing salt concentration in irrigation water but the growth was not harmfully affected at lower levels of salinity. Plant height and biomass was significantly decreased irrigating with water containing salinity 10.79 dS m-1.After harvest it was found that irrigation with saline water up to 10.79 dS m-1 did not show any increase of soil salinity. It was probably due to rainfall during the monsoon which was occurred at the later stage of the growing period. So, the fodder sorghum plant might be cultivated in the coastal regions of Bangladesh where fresh water irrigation is limited due to salinity problem as well as might be grown irrigating with saline water up to 10.79 dS m-1.SAARC J. Agri., 16(1): 145-155 (2018)